The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tme.12640
|View full text |Cite
|
Sign up to set email alerts
|

Blood product wastage reduction by utilising low‐cost, low‐impact multimodal physician‐to‐physician communication initiatives

Abstract: Objectives:To assess a multimodal physician-to-physician communication initiative that is low in cost and impact to daily workflow to reduce blood product wastage.Background: Blood product stewardship is an important issue in all hospital systems. Previous studies have proposed low-cost interventions to reduce blood product wastage, but few have evaluated improvements in communication between the blood bank and providers. We undertook a prospective quality improvement project focusing on improving communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To reduce blood wastage and enhance stock management, a number of low-cost policies can be implemented. These include improved communication between blood banks and providers ( Levin et al, 2019 , Mishra et al, 2021 ), staff continual education ( Burk et al, 2021 ), improved transport Kron et al, 2021 ), and updating transfusion protocols ( Bawazir and Dakkam, 2020 , Gholami et al, 2021 ) which all have been proven to have a cumulative effect in reducing blood wastage.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce blood wastage and enhance stock management, a number of low-cost policies can be implemented. These include improved communication between blood banks and providers ( Levin et al, 2019 , Mishra et al, 2021 ), staff continual education ( Burk et al, 2021 ), improved transport Kron et al, 2021 ), and updating transfusion protocols ( Bawazir and Dakkam, 2020 , Gholami et al, 2021 ) which all have been proven to have a cumulative effect in reducing blood wastage.…”
Section: Discussionmentioning
confidence: 99%
“… 72 A recent study by Levin et al showed that even a low-cost initiative such as physician-to-physician communication could significantly reduce blood product wastage. 73 In a dwindling donor supply setting, there is a greater need to promote PBM as a standard of care.…”
Section: Role Of Patient Blood Managementmentioning
confidence: 99%
“…Journal of Blood Medicine 2023:14 606 communication could significantly reduce blood product wastage. 73 In a dwindling donor supply setting, there is a greater need to promote PBM as a standard of care.…”
Section: Dovepressmentioning
confidence: 99%
“…[9][10][11][12][13] This modification of ordering practice is accomplished through educational initiatives that encourage adherence to local transfusion thresholds and promote the appropriate correction of preoperative anemia. [14][15][16][17][18] However, even appropriately placed blood orders can contribute to unnecessary blood component and product wastage.…”
Section: Introductionmentioning
confidence: 99%